2021
DOI: 10.2298/vsp191212014m
|View full text |Cite
|
Sign up to set email alerts
|

The advantages and disadvantages of biodentine: Satisfactory mechanical properties and radiopacity not meeting ISO standard

Abstract: Background/ Aim. The aim of this study was to characterize the physicochemical properties of the commercially available calcium silicate based dental cement Biodentine (Septodont). Methods. Material elucidation included measurements of radiopacity, scanning electron microscopic and x-ray dispersive analyses, wettability, Fourier transform infrared spectroscopy, microindentation, micro-to nano-porosity, setting time, pH and calcium ion release. Cells were grown on Biodentine surface in order to evaluate its beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
2
0
1
Order By: Relevance
“…This is different from the manufacturer's claims that the material possesses a radiopacity of 3.5 mm AI, complying with the ISO standard. Our results were in agreement with a number of other studies [46][47][48][49][50], which reported similar radiopacity values for Biodentine. According to Camilleri and Sorrentino [51], 5.1 wt% of zirconium oxide has been detected as a radiopacifier in Biodentine powder to facilitate detection on radiographs.…”
Section: Discussionsupporting
confidence: 93%
“…This is different from the manufacturer's claims that the material possesses a radiopacity of 3.5 mm AI, complying with the ISO standard. Our results were in agreement with a number of other studies [46][47][48][49][50], which reported similar radiopacity values for Biodentine. According to Camilleri and Sorrentino [51], 5.1 wt% of zirconium oxide has been detected as a radiopacifier in Biodentine powder to facilitate detection on radiographs.…”
Section: Discussionsupporting
confidence: 93%
“…With regards to the capping material, MTA is considered the gold standard material in vital pulp therapy (17) . While, Biodentine has a short setting time and is easy to mix, apply, and has excellent mechanical properties in addition to its bioactive properties (18) . No significant difference was found between MTA and Biodentine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, modern strategies for bio-activation of the surfaces of titanium implants include their coating with Sr incorporated layers. Secondly, Sr is intentionally used in the form of carbonates since the addition of calcium carbonate (CaCO 3 ) into CS cements decreases setting time, as it was achieved in Biodentine (Septodont, France) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Takođe, savremene strategije za povećanje bioaktivnosti površina titanijumskih implantata uključuju njihovo presvlačenje filmovima na bazi stroncijuma. Drugo, stroncijum je sa razlogom odabran u formi karbonata jer dodavanje kalcijum-karbonata u KS cemente skraćuje vreme očvršćavanja, što je postignuto kod biodentina (Septodont, Francuska) [27].…”
Section: Acknowledgesunclassified